Prevalence and associated factors of skin diseases among geriatric outpatients from a metropolitan dermatologic clinic in Thailand - Jedpakorn Laopakorn; Sujirod Hanthavichai (Wolters Kluwer Medknow Publications, 2022)
Background: The importance of the geriatric population has been increasing expeditiously in the health-care system. The epidemiology of skin disorders is an interesting subject to challenge physicians to comprehensively manage the elderly. Objectives: The objective of the study was to determine the prevalence of the most frequent dermatologic disorders among elderly outpatients and identify major associated determinants. Methods: This retrospective observational study recruited subjects aged 60 years and older attending the dermatologic clinic at the Faculty of Medicine, Vajira Hospital, in Thailand. The medical records were collected between January 2017 and December 2020. The data were analyzed according to age, sex, season, underlying medical diseases, and areas of involvement to identify the associated factors for the frequently presented dermatologic diagnoses. Results: In this study, 521 outpatients (including 218 males and 303 females) with a mean age of 71.34 years (range, 60-04 years) were enrolled. The most common dermatoses were eczematous dermatitis (35.7%), cutaneous infection (18.2%), xerosis (15.5%), and psoriasis (7.3%). The distribution of the prevalent dermatologic disorders still did not change during the COVID-19 pandemic. A significant association was found between xerosis and age of 80 years and older (odds ratio [OR], 2.03; 95% confidence interval [CI], 1.09-3.78; P = 0.026). The risk of developing xerosis cutis significantly decreased with dyslipidemia (OR, 0.45; 95% CI, 0.26-0.78; P = 0.004). Conclusion: The three foremost cutaneous disease groups are eczematous dermatitis, skin infection, and xerosis cutis. Dry skin is strongly connected with the age of 80 years and above; however, xerosis is coincidentally correlated with dyslipidemia.